Updated approach for the management of osteoporosis in Turkey: a consensus report - YAVUZ, DİLEK (SPRINGER LONDON LTD, 2020)
As a result of the current demographics, increased projections of osteoporosis (OP) and prevalence of the disease in Turkey, a panel of multidisciplinary experts developed a thorough review to assist clinicians in identifying OP and associated fracture risk patients, diagnosing the disease with the appropriate available diagnostic methods, classifying the disease, and initiating appropriate treatment. The panel expects to increase the awareness of this prevalent disease, decrease consequences of OP with corresponding cost savings and, ultimately, decrease the overall burden of OP and related fractures in Turkey. Background OP is not officially accepted as a chronic disease in Turkey despite the high prevalence and predicted increase in the following years. However, there are areas where the country is performing well, such as having a country-specific fracture risk assessment model, DXA access, and the uptake of FRAX. Additional efforts are required to decrease the existing treatment gap estimating 75-90% of patients do not receive pharmacological intervention for secondary prevention, and the diagnosis rate is around 25%. Methods A selected panel of Turkish experts in fields related to osteoporosis was provided with a series of relevant questions to address prior to the multi-day conference. Within this conference, each narrative was discussed and edited by the entire group, through numerous drafts and rounds of discussion until a consensus was achieved. Represented in the panel were a number of societies including The Turkish Osteoporosis Society, The Society of Endocrinology and Metabolism of Turkey (SEMT), and The Turkish Society of Physical Medicine and Rehabilitation. Results Standardized general guidelines to identify OP and related fractures and at-risk population in Turkey, which will enable clinicians to accurately and effectively diagnose the disease, treat the appropriate patients with available pharmacological and non-pharmacological treatments and decrease the burden of the disease. Conclusions This manuscript provides a review of the current state of OP and related fractures in Turkey. Moreover, this manuscript reviews current international guidelines and national studies and proposes a number of helpful country-specific classifications that can be used by healthcare providers caring for the at-risk population. Additionally, the panel proposes practical recommendations that should be implemented nationally in order to decrease the burden of OP and related fractures and effectively preventing the burden in future generations.
Keywords: Diagnosis of osteoporosis; Treatment of osteoporosis; Fracture risk assessment; FRAX; VITAMIN-D; CALCIUM SUPPLEMENTATION; POSTMENOPAUSAL WOMEN; HIP FRACTURE; CONTROLLED-TRIAL; RISK-FACTORS; BONE; PREVENTION; DXA; PERFORMANCE